The production and release of microcystin related to phytoplankton biodiversity and water salinity in two cyanobacteria blooming lakes. (23rd July 2018) - Jia, Junmei; Chen, Qiuwen; Wang, Min; Zhang, Jianyun; Yi, Qitao; Hu, Liuming
Abstract: To find the connections between microcystins and the phytoplankton community, coupled with environmental factors, we investigated 2 cyanobacteria blooming lakes, Lake Taihu (at the center of the Yangtze River Delta, eastern China) and Lake Yanghe (near Qinhuangdao City, northern China). Two years of data, including water quality and the amounts of phytoplankton, microcystins, and the congeners in both algal cells and water, were collected from the 2 lakes during 2013 and 2014. The results showed that both the microcystin quota and release percentage were positively correlated with biodiversity of phytoplankton and the Chlorophyta to phytoplankton ratio, but were negatively correlated with cyanobacteria abundance and the cyanobacteria to phytoplankton ratio; both the microcystin quota and release percentage were closely related to the intensity of competition between cyanobacteria and other phytoplankton; meanwhile, microcystins played a role in the competition between cyanobacteria and other phytoplankton. Salinity had a significantly negative relationship with both cellular and total microcystins, but a significantly positive relationship with the microcystin releasing percentage, indicating that an increase in salinity inhibited the production of microcystins but promoted their release into the aquatic environment. In addition, the average number of microcystins in Lake Yanghe was several times higher than the provisional guideline value adopted by the World Health Organization, indicating a possible health risk to local people. Environ Toxicol Chem 2018;37:2312–2322. © 2018 SETAC.